APPLICATION OF SIKUAT IN HEALTH SERVICES AT PUSKESMAS CANDI DISTRICT SIDOARJO REGENCY - Kusumo, Ibnu Hadi; Sukmana, Hendra (ANTIS PUBLISHER, 2024)
General Background: The integration of technology in healthcare systems has become essential for improving service efficiency and quality. Health information systems, like the SiKuat application, are increasingly being adopted in public health centers to enhance healthcare delivery. Specific Background: The SiKuat application is a health information system developed to streamline healthcare services at public health centers. However, its effectiveness in practice, particularly in resource-constrained settings like the Candi District Public Health Center, remains under-explored. Knowledge Gap: Despite its potential, there is limited research on the real-world challenges and benefits associated with the implementation of SiKuat in public health centers, especially concerning technical infrastructure and human resource limitations. Aims: This study aims to analyze the implementation and impact of the SiKuat application in healthcare services at the Candi District Public Health Center, Sidoarjo Regency. Results: The study found that the SiKuat application positively impacted healthcare services by improving patient data access, medication stock monitoring, and medical record accuracy. It also facilitated more organized administrative management. However, challenges such as a lack of skilled personnel and occasional technical disruptions were observed. Novelty: This research contributes new insights into the practical application of the SiKuat system, particularly in terms of its impact on operational efficiency and the barriers to its full utilization in a public health center setting. Implications: The findings suggest that while SiKuat has the potential to improve healthcare services, successful implementation requires ongoing training for healthcare staff and infrastructure improvements to overcome the existing challenges.